Enabling the High‐Voltage Operation of Layered Ternary Oxide Cathodes via Thermally Tailored Interphase. Issue 4 (3rd March 2022) - Zhu, Zhiqiang; Cao, Shengkai; Ge, Xiang; Xi, Shibo; Xia, Huarong; Zhang, Wei; Lv, Zhisheng; Wei, Jiaqi; Chen, Xiaodong
Abstract: Layered ternary oxides LiNi x Mn y Co z O2 are promising cathode candidates for high‐energy lithium‐ion batteries (LIBs), but they usually suffer from the severe interfacial parasitic reactions at voltages above 4.3 V versus Li + /Li, which greatly limit their practical capacities. Herein, using LiNi1/3 Mn1/3 Co1/3 O2 (NMC111) as the model system, a novel high‐temperature pre‐cycling strategy is proposed to realize its stable cycling in 3.0−4.5 V by constructing a robust cathode/electrolyte interphase (CEI). Specifically, performing the first five cycles of NMC111 at 55 ° C helps to yield a uniform CEI layer enriched with fluorine‐containing species, Li2 CO3 and poly(CO3 ), which greatly suppresses the detrimental side reactions during extended cycling at 25 ° C, endowing the cell with a capacity retention of 92.3% at 1C after 300 cycles, far surpassing 62.0% for the control sample without the thermally tailored CEI. This work highlights the critical role of temperature on manipulating the interfacial properties of cathode materials, opening a new avenue for developing high‐voltage cathodes for Li‐ion batteries. Abstract : Performing a high‐temperature pre‐cycling process for the LiNix Mny Coz O2 (NMC) cathode materials helps to yield a uniform and robust cathode/electrolyte interphase, which could suppress parasitic interfacial reactions in subsequent cycling, enabling Li‐ion battery operation in high voltage conditions with good cyclic stability.